Pengaruh Model Project Based Learning Berbantuan Wordwall terhadap Kemampuan Berpikir Kritis Siswa Materi Gaya Gravitasi pada Kelas IV SDN Ciracas 10 Pagi - Annisa Ghassani Qonita; Sri Lestari Handayani (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Critical thinking skills can be pursued in various ways, one of which is by applying innovative learning models. The purpose of this study was to examine how the Wordwall-assisted Project-Based Learning Model was applied to the gravity material for Class IV SDN Ciracas 10. There were 64 participants in this study: 32 from the experimental group IV-C and 32 from the control group IV-B. The data passed the normality test which was carried out using the Shapiro-Wilk Liliefors distribution before being analyzed and the homogeneous test with Fisher's test with homogeneous results. Statistical results in this study the control class obtained 70.13 and the experimental class 79.78, which means that there was an influence on the research